Overnight Continuous Saline Bladder Irrigation After En Bloc Resection of Bladder Tumor Does Not Improve Oncological Outcomes in Patients Who Have Received Intravesical Chemotherapy - Yang, Yongjun; Liu, Chao; Yan, Xiaoting; Li, Jiawei; Yang, Xiaofeng (Frontiers in Oncology, 2021)
Objective To evaluate the safety and efficacy of overnight continuous saline bladder irrigation (CSBI) for patients who have received thulium laser en bloc resection of bladder tumor (TmLRBT) combined with immediate intravesical chemotherapy previously. Methods From October 2014 to June 2018, 235 patients with newly diagnosed non-muscle invasive bladder cancer (NMIBC) were included in this retrospective study. All patients received intravesical instillation of pirarubicin immediately after TmLRBT. The patients were divided into two groups according to the duration of postoperative bladder irrigation with normal saline. After immediate intravesical chemotherapy, patients in group 1 received overnight CSBI, while patients in group 2 did not receive overnight CSBI. Data on the time of initial tumor recurrence, recurrence-free survival (RFS) and progression-free survival (PFS) rates, and perioperative complications were collected and analyzed. Results Of 235 included patients (129 in group 1 and 106 in group 2), the median follow-up periods were 42 months and 38 months, respectively. There were no significant differences in patients' baseline characteristics between the two groups. The RFS rates of patients in group 1 were 90.7%, 82.7% and 76.8% at the end of the first, third and fifth years, while the corresponding RFS rates of patients in group 2 were 87.7%, 78.9% and 73.3%, respectively. Four patients in group 1 and five patients in group 2 experienced tumor progression. No significant differences between the two groups were observed in the time of initial tumor recurrence, RFS and PFS rates. Only Grade I complications occurred in the two groups, and no significant difference was reached between the two groups. Conclusions For patients with NMIBC who have previously received TmLRBT combined with immediate intravesical chemotherapy, overnight CSBI may not improve oncological outcomes and reduce perioperative complications.